In situ57Fe mössbauer study of a porphyrin based FeNC catalyst for ORR. (1st November 2021) - Ni, Lingmei; Theis, Pascal; Paul, Stephen; Stark, Robert W.; Kramm, Ulrike I.
Abstract: FeNC catalysts are important substitutes for the oxygen reduction reaction (ORR) in fuel cells. This work reports on an in situ Mössbauer spectroelectrochemical study of a porphyrin-based catalyst. Activity and selectivity towards ORR were determined from rotating ring disc electrode (RRDE) experiments at different loadings in acidic electrolyte and accompanied by H2 O2 oxidation reduction measurements in order to identify the contributions to the different ORR pathways as function of potential. The comparison to in situ 57 Fe Mössbauer spectra enables an assignment of these contributions to the iron signatures. The results indicate that two different "onset potentials" for obtaining the deoxygenated state associated with two different iron environments can be identified and being associated with the selectivity data. Moreover, the in situ data enable the determination of mass-based site density and turn-over frequency data for ORR relevant conditions. As a consequence, this work sheds light on the oxygen reduction reaction mechanism involved in FeNC catalysts.